Students Do Read Better Today? - Fry, Edward ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
Despite widely-held beliefs to the contrary, three different sources of research data prove that children in the 1990s read better on the average than either their father's generation or their grandfather's generation. "Then and Now" studies indicate that students read better now than decades ago. Restandardization of test norms also indicate an improvement of reading ability. In the only large study planned to show change over time, the National Assessment of Educational Progress (NAEP) measured the reading ability of 9 year olds, 13 year olds, and 17 year olds every few years between 1971 and 1990. Considering the vast demographic shifts, NAEP's finding that there was no significant change in reading ability between 1971 and 1990 is a testimonial to the ability of United States reading teachers. Reading teachers should read reports of NAEP studies with extreme caution. On first appearance it looks like U.S. students are doing poorly, but on careful reading, all that is happening is that some unknown "they" have set "proficiency standards" that "they" would like all students to meet. Comparative data in the NAEP study indicates that school children in California, which adopted a new framework for language arts instruction in 1987, scored near the bottom on the assessment. Readers of news media reports of NAEP reports should use all their critical reading skills: they should not confuse hard core comparative data with somebody's expectations which might be called "standards" or "proficiency levels." (RS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Trends; Elementary Secondary Education; Reading Ability; Reading Achievement; Reading Research; Reading Tests; Standardized Tests; Test Norms; California -- National Assessment of Educational Progress; Opinion Papers; Reports, Descriptive